Comparative study on viscosity and drag reducing performance between hydroxypropyl cellulose and hydroxypropyl cellulose-surfactant mixture - Moreton-Shabirin, Ainoon; A Abdulbari, Hayder (International Journal of Engineering and Technology, 2019)
Ammonium Chloride (BZK) was found to enhance the drag reduction performance of a semi-rigid polymer Hydroxypropyl cellulose (HPC) in turbulent pipe flow. Rheology test showed that HPC’s viscosity was higher than that of HPC-BZK mixture, and this showed that the presence of BZK had weakened the intermolecular strength of HPC molecules. Pressure-drop measurements indicated that HPC’s and HPC-BZK mixture’s drag reducing performance are (a) dependent on Reynolds number, and these mildly enhanced in the presence of BZK and (b) weakly dependent on additives concentration. Both HPC and HPC-BZK mixture showed a maximum drag reduction of 27% and 31%, respectively at Reynold’s no. 59448 and gradual degradation thereafter. Although the presence of BZK enhanced the drag reduction performance of HPC in the mixture form, the experimental data indicated that BZK did not extend HPC’s drag reduction performance nor assist the HPC to re-assume itself following structural degradation.
Keywords: Drag reduction; Surfactant; Rigid Polymer.